Metal-decorated 3D tin oxide nanotubes in a monolithic sensor array chip for room-temperature gas identification - Yan, Jia; Song, Zhilong (Journal of alloys and compounds, 2024)
Inadequate limit of detection at room temperature and unsatisfactory selectivity remain challenge for wide applications of the chemiresistive gas sensors. Nanostructured gas sensors ensure the desirable activation energy for the gas adsorption and chemical reactions, favorable for room-temperature parts-per-billion (ppb) level gas detection. In this work, we demonstrated a single-chip integrated gas sensor array (4 ×4 pixels) based on kinds of metal (Pt, Pd, Au, Ag) decorated 3D SnO2 nanotubes for ultrasensitive room-temperature gas-sensing. The nanostructured sensor array has a high surface area-to-volume ratio, enabling room temperature sensing with high detection response toward H2 (minimum 5 ppm), formaldehyde (minimum 50 ppb), toluene (minimum 50 ppb) and NO2 (minimum 100 ppb) with the detection accuracy within 5% range, respectively. In addition, the effect of metals decoration on the gas identification features were systematically conducted, and these specific response features can be mainly attributed to metal activation capability toward the gases, which enables demonstrating differentiable response patterns for the target gases identification employing a pattern recognition algorithm. These results demonstrate that the proposed strategy helps to provide an excellent route for the future low-power-consumption smart sensing devices design and fabrication. •Metal-decorated 3D tin oxide nanotubes sensor array chip was realized.•The sensor array enables room temperature gas sensing with high detection accuracy.•The sensor array enables achieving gas identification in the specific circumstances.